The origins of Russophobia: on the issue of social and political culture of interstate relations - D. A. Kalashaova; A. A. Bezrukova; A. K. Tkhakushinov (Вестник Майкопского государственного технологического университета)
The article examines the concept and implementation of the principle of «Russophobia» as a type of socio-cultural intolerance. The relevance of addressing this topic is justiﬁed by the modern realities of the socio-political confrontation of Western countries in relation to Russia. Particular attention is paid to the causes of Russophobia and the main trends in its manifestation in the modern world. The research was carried out using the method of socio-historical analysis, the epistemological method of analyzing literary, journalistic and scientiﬁc sources. The research examines concepts formed in different periods of history that comprehend this phenomenon. Based on reﬂections on Russophobia by authoritative Russian philosophers, writers and publicists, it has been proved that the Russophobic narrative, starting from the 16th century, became a stable ideological trend reﬂecting the expansionist interests of Western elites. As Russia strengthened on the world stage, Russophobia intensiﬁed. The ideological «crusade» against Orthodox Rus' was launched by European travelers of the 17th-19th centuries, who created a negative image of our country in the Western world. Currently, the countries of the united West have declared a «sacred war» against Russia. A powerful propaganda campaign was launched, directed against Russia and everything Russian. The authors of the article give a moral and ethical assessment of the sociopolitical processes of a new surge of Russophobia in modern conditions. It is suggested that in the current conditions it is necessary to carry out an open international ﬁght against Russophobia and create a system of our own channels of inﬂuence in the Western information space, as well as counteract internal Russophobia using cultural and educational methods.